AN INTEGRATIVE MOSQUE EMPOWERMENT MODEL FOR ENHANCING COMMUNITY WELFARE: A CASE STUDY OF THE JAMI' HASANUDIN SABBIHISMA RABBIKAL A'LA MOSQUE IN PADANG PARIAMAN - Saddam Hakki; Sri Wahyu Ningsih (Journal of Social Science, 2026)
Objective: This study aims to investigate the role of the mosque as a religious institution in driving the socio-economic empowerment of the community, drawing upon a case study of the Jami' Hasanudin Sabbihisma Rabbikal A'la Mosque in Katapiang, Padang Pariaman. This inquiry is highly significant, as the current discourse on mosque-based empowerment remains predominantly governed by normative approaches, while empirical studies elucidating socio-economic empowerment practices at the localized level remain relatively scarce. Method: Utilizing a qualitative approach alongside a case study methodology, this research seeks to comprehend how mosque-implemented programs contribute to the advancement of congregational welfare. Data were systematically gathered through observation, in-depth interviews, and the documentation of various mosque activities. Results: The findings reveal that the mosque's function has evolved significantly beyond a mere ritualistic role, emerging as a central hub for community empowerment through social assistance programs, religious cultivation, the reinforcement of social solidarity, and the administration of productive business units capable of generating employment for the public. These multifaceted initiatives not only stimulate congregational participation but also sustainably fortify the social and economic capacities of the community. Novelty: Ultimately, the findings of this study substantiate that mosques harbor strategic potential as community-based agents of social change, uniquely positioned to integrate spiritual, social, and economic functions. This research thereby contributes to the broader academic literature on mosque-based community empowerment by supplying empirical evidence of a viable socio-economic empowerment model, which may serve as a benchmark for the formulation of analogous programs in other local community contexts.